Childhood emotional neglect and problematic mobile phone use among Chinese adolescents: A longitudinal moderated mediation model involving school engagement and sensation seeking. (May 2021) - Chen, Yuanyuan; Zhang, Yibo; Zhang, Lilan; Luo, Fangzhou; Xu, Wanting; Huang, Jiahui; Yang, Liyu; Zhang, Wei
Abstract: Background: Childhood emotional neglect has been shown to be associated with a range of emotional, behavioral and social problems. We hypothesized that childhood emotional neglect might predispose adolescents to engage in Problematic Mobile Phone Use (PMPU) as a way to meet their needs for relatedness. Objective: Using a longitudinal design, we aimed to reveal the explanatory mechanism in the association between childhood emotional neglect and PMPU among Chinese adolescents, by testing the mediating effect of school engagement and the moderating effect of sensation seeking. Methods: Participants were 1987 Chinese adolescents (56.13 % male; Mage at Wave 1 = 12.32) who completed self-report questionnaires regarding childhood emotional neglect, school engagement, PMPU and sensation seeking at three time points in the course of a year. Results: The results of structural equation modeling (SEM) showed that retrospective reports of childhood emotional neglect at Wave 1 were positively associated with adolescent PMPU at Wave 3, and school engagement at Wave 2 fully mediated the association. Meanwhile, sensation seeking at Wave 3 moderated the pathway from school engagement to later adolescent PMPU in the mediated model. Specifically, the effect of low school engagement on PMPU was stronger for adolescents who reported high sensation seeking. Conclusion: Identifying the processes by which childhood emotional neglect is associated with adolescent PMPU over time has potential applied value for prevention and intervention.